Comparison of Jack Knife Stretching and Miofacial Decompression on Increasing Hamstring Muscle Flexibility in Futsal Players - Arsifanto, Achid Muyassar; Wahyuni, Wahyuni (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Flexibility plays an important role for athletes, especially football players. The greater a person's level of muscle flexibility, the lower the risk of injury. Jack Knife Stretching (JKS) and Myofascial Decompression (MD) are treatments that help promote flexibility, particularly for the hamstring muscles. This study aimed to eaxamine the effect of Jack Knife Stretching and Myofascial Decompression in enhancing hamstring muscular flexibility in futsal players.Subjects and Method: This was a randomized controlled trial. The study was conducted at the Kendal Football Club, Kendal, Central Java, Indonesiea, on June 2023. A sample of 20 football players was selected and divided into two groups randomly. The dependent variable was hamstring muscle flexibility. The independent variables were Jack knife stretching and myofascial decompression. Hamstring muscle flexibility was examined using V sit and reach test. Data were compared using independent t test.Results: Before intervention, hamstring muscle flexibility score between groups were comparable (p= 0.708). After intervention, hamstring muscle flexibility score in the MD group (Mean= 22.41; SD= 0.61) was higher than JKS group (Mean= 20.42; SD= 1.36), and it was statistically significant (p= 0.026).Conclusion: Myofascial decompression is more effective to increase hamstring muscle flexibility than Jack knife stretching. Keyword: muscle flexibility, Jack knife stretching, myofascial decompression